New Professional Competencies and Skills Leaning towards Industry 4.0 - Moura, Roque Antonio [UNESP]; Richetto, Marco Rogerio Silva [UNESP]; Luche, Daniela Ercole Dale [UNESP]; Tozi, Luiz Antonio; Silva, Messias Borges [UNESP]; Cukurova, M.; Rummel, N.; Gillet, D.; McLaren, B.; Uhomoibhi, J. (Scitepress, 2022)
Industry 4.0, the so-called fourth industrial revolution, has been popularized by a German government project to promote digitization and automation, and has become a global strategy disseminated throughout several countries. It is widely used by researchers and mentors in different contexts and studies on opportunities, risks and challenges concerning employability. Therefore, this study aims to address the challenges of recruiters in the face of trends in new skills, profiles, and professional competencies for safeguarding jobs. Its method involves a systematic literature review using the keywords Human and Machine Learning and Industry 4.0 and Education. Bibliometrics was performed on works published on the theme during the latest decade. Results demonstrate the importance of updating Human Resources and Educational policies within the development of new skills and competencies to meet the new professional profile requirements and ensure human employability.
Keywords: Employability; Human Resources; Industry 4.0; New Competencies; New Skills